Compliance, efficacy, and safety of subcutaneous and sublingual immunotherapy in children with allergic rhinitis. Issue 1 (14th September 2020) - Liu, Wenlong; Zeng, Qingxiang; He, Chunhui; Chen, Rongshan; Tang, Yiquan; Yan, Shengbao; Luo, Xi; Luo, Renzhong
Abstract: Background: Although previous studies had confirmed the effectiveness and safety of subcutaneous immunotherapy (SCIT) and sublingual immunotherapy (SLIT), respectively, direct head‐to‐head comparison of SCIT vs SLIT is sparse. We aimed to compare the efficacy, safety, and compliance of SCIT and SLIT in allergic rhinitis (AR) children. Methods: This study is a prospective, open‐label, and single‐center study performed between June 2017 and June 2018. A total of 325 children were grouped into SLIT, Alutard (SCIT1), and NovoHelisen Depot (NHD) (SCIT2) according to the parents' wishes. The adherence and reasons for dropout were recorded. The efficacy of SLIT and SCIT was evaluated by a combined symptom medication score. Adverse events (AEs) were recorded and graded during the whole treatment. Results: The compliance rate was higher in the SCIT group compared with the SLIT group ( P  < .05). The total nasal symptom score (TNSS), rescue medication score (RMS), and symptom medication score (SMS) after 6‐month, 12‐month, and 2‐year treatment were lower in the SCIT group compared with the SLIT group ( P  < .05). But the scores between the Alutard and NHD groups were not significantly different. The occurrence of AEs in the SCIT group was significantly higher compared with the SLIT group ( P  < .05). Conclusion: Our results suggested SCIT is more effective compared with SLIT to a certain degree, whereas SLIT had less AEs compared with SCIT. The AIT routes can be chosen according to personal specific conditions.